Role of Digital Library in Homeopathic Education in India - Vaja, Bharti L; Sharma, Parmest Vishnu Kumar (Journal of Advanced Research in Library and Information Science, 2020)
The rapid advancement in Information Technologies has revolution the only of libraries. Information Technology has its own niche in every aspect of life within the society. Changes in society & technology made variation within the life sort of Indian people and their views & attitude towards the libraries. Today digital world cares, with creating, sharing & using information in digital form. Information Technology has almost converted the earth into a worldwide village. Digital libraries has brought phenomenal change within the progress of collection, storage, preservation of rare documents, retrieval & dissemination of data Now –a-days the ICT is taken under consideration as an important commodity and is playing an important sole for development altogether fields like education, research etc. this study focuses on the functional aspect of the digital library in homoeopathy education in India. within the present education system, digital libraries are playing a key role in disseminating information by providing differing types of relevant & recent information to the users with a brief span of your time. The digital library can provide open access to the electronic information sources and therefore the users can access the digital content regardless of time & space boundaries. This study also discusses the core elements and functional components of the digital library in homoeopathy education.